The history of olive cultivation in the southern Levant - Barazani, Oz; Dag, Arnon; Dunseth, Zachary (Frontiers in Plant Science, 2023)
The olive tree (Olea europaea L. subsp. europaea var. europaea) is one of the most important crops across the Mediterranean, particularly the southern Levant. Its regional economic importance dates at least to the Early Bronze Age (~3600 BCE) and its cultivation contributed significantly to the culture and heritage of ancient civilizations in the region. In the southern Levant, pollen, pits and wood remains of wild olives (O. europaea L. subsp. europaea var. sylvestris) has been found in Middle Pleistocene sediments dating to approximately 780 kya, and are present in numerous palynological sequences throughout the Pleistocene and into the Holocene. Archeological evidence indicates the olive oil production from at least the Pottery Neolithic to Chalcolithic transition (~7600-7000 BP), and clear evidence for cultivation by 7000 BP. It is hypothesized that olive cultivation began through the selection of local genotypes of the wild var. sylvestris. Local populations of naturally growing trees today have thus been considered wild relatives of the olive. Ancient olive landraces might thus represent an ancient genetic stock closer to the ancestor gene pool. However, millennia of cultivation raises questions about whether genuine populations of var. sylvestris remain in the region. This review summarizes the evidence supporting the theory that olives were first cultivated in the southern Levant and reviews our genetic work characterizing local ancient cultivars. The significance and importance of old cultivars and wild populations are discussed, given the immediate need to adapt agricultural practices and crops to environmental degradation and global climate change.